Eksperimen Strategi Pembelajaran Student Teams Achievement Divisions (Stad) Terintegrasi Teams Games Tournaments (Tgt) Terhadap Hasil Belajar Matematika Ditinjau Dari Keaktifan Siswa Kelas Vii Smp N 1 Sawit Tahun Ajaran 2016/ 2017 - Sarwasih, Siwi; , Muhammad Noor Kholid,S.Pd.,M.Pd (2017)
This research three purpose, (1) examine the effect of learning strategies toward mathematics learning outcomes, (2) examine the effect of the level of activity toward mathematics learning outcomes, and (3) examine interaction between learning strategies and the level of activity toward mathematics learning outcomes. The type of this research is quantitative with quasi-experimental design. The population in this research consisted of three classes there are first experiment class, second experiment class, and control experiment with the sampling technique using cluster random sampling. Methods of data collection used documentation, questionnaire, and test. Tecniques of analyzed used analysis of variance two paths with different cell with a significance level of 5%. Result of the data analysis was obtained: (1) there is a effect of learning strategies toward mathematics learning outcomes, (2) there is a effect level of activity toward mathematics learning outcomes, and (3) there is no interaction between the learning strategies, and level of activity toward mathematics learning outcomes. Keyword: learning strategies, level of activity, mathematics learning outcomes.